2021
DOI: 10.1177/00037028211038634
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Manganese in Underwater Steel Samples Using Long–Short Double-Pulse Laser-Induced Breakdown Spectroscopy

Abstract: The long–short double-pulse laser-induced breakdown spectroscopy (LS-DP-LIBS) method was applied to qualitative and quantitative analyses of underwater steel samples to improve the detection ability of underwater measurement. The stable plasma intensity and discrete emission lines were detected using LS-DP-LIBS when comparing the measured results of single-pulse LIBS (SP-LIBS) and LS-DP-LIBS. The long pulse produces a cavitation bubble without plasma, and the short pulse induces the plasma of steel samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The other paper by that group compared the long-short double pulse version of LIBS with conventional single pulse LIBS. 22 The long-short double pulse version gave a better stability and this was attributed to the long pulse causing a cavitation bubble without a plasma and then the short pulse creating a plasma within the bubble. The LIBS parameters of intra-pulse delay time, long pulse width and delay time were optimised.…”
Section: Ferrous Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other paper by that group compared the long-short double pulse version of LIBS with conventional single pulse LIBS. 22 The long-short double pulse version gave a better stability and this was attributed to the long pulse causing a cavitation bubble without a plasma and then the short pulse creating a plasma within the bubble. The LIBS parameters of intra-pulse delay time, long pulse width and delay time were optimised.…”
Section: Ferrous Metalsmentioning
confidence: 99%
“…Two papers by the same research group have discussed the application of long-short, double pulse LIBS to the determination of Mn in underwater steel samples. 21,22 In the first example, by Cui et al , it was emphasised that underwater LIBS suffers from numerous problems including self-absorption effects, weak signal intensity and low lifetime of the signal. These could all be overcome using Fraunhofer-type lines.…”
Section: Metalsmentioning
confidence: 99%
“…On-site elemental analysis of submerged solids or dissolved species can be achieved by measuring the emission spectrum of the plasma produced by laser ablation (e.g., ref. [1][2][3][4][5][6][7] or laserinduced breakdown (e.g., ref. [8][9][10][11][12][13][14] in liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Qingdong et al found that the quantitative analysis accuracy of a fiberoptic LIBS system was slightly higher than that of a traditional LIBS system and a portable LIBS system [11,12]. Experimental parameters such as laser energy, delay time and resolution are also factors that researchers have often considered [13,[14][15][16]. Khater et al searched for stable conditions suitable for spectrochemical analysis by changing the laser energy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis is also an important research area in LIBS spectral analysis. Quantitative analysis is helpful to understand the concentration of elements in the material and is helpful for industrial analysis [13,23,24]. It is very important to study the influencing factors of quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%